PENGARUH MODEL PEMBELAJARAN PBL TERHADAP HASIL BELAJAR SISWA KELAS IX.11 DI MAN 2 KOTA SUKABUMI PADA MATA PELAJARAN FIQIH: The Transformation of Fiqh Learning Based on Problem-Based Learning to Strengthen Students' Cognitive, Affective, and Psychomotor Domains - Zaki, Muhammad; Nurdiana, Putri; Agustina, Risa; Premitha, Septy (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
The quality of Fiqh instruction at the Madrasah Aliyah level continues to face challenges, particularly in fostering student engagement and deep conceptual understanding of normative-reflective content. This study aims to evaluate the effectiveness of the Problem-Based Learning (PBL) model in improving student learning outcomes on the topic of